2019
DOI: 10.1097/gox.0000000000002374
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoplasty and External Nasal Splinting: Is It Really a Must?

Abstract: Background:Rhinoplasty is a common and challenging procedure. Lateral osteotomy is routinely performed in most cases. Most of the surgeons have the habit of applying external nasal splints to stabilize the nasal tissues and bone in their new position postrhinoplasty. These splints are widely used despite the absence of any evidence supporting this practice. Moreover, these splints have a lot of disadvantages, so we conducted this study to evaluate the cosmetic result in their absence.Patients and Methods:A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This was consistent with our study, where patients suffered from only a mild edema and ecchymosis that resolved in the coming week of fat filling. On the other side, surgical rhinoplasty presented other complications such as skin necrosis and infection 26 . To note that a secondary surgical rhinoplasty can aggravate the shape of nose and make it more difficult to correct 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with our study, where patients suffered from only a mild edema and ecchymosis that resolved in the coming week of fat filling. On the other side, surgical rhinoplasty presented other complications such as skin necrosis and infection 26 . To note that a secondary surgical rhinoplasty can aggravate the shape of nose and make it more difficult to correct 27 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, surgical rhinoplasty presented other complications such as skin necrosis and infection. 26 To note that a secondary surgical rhinoplasty can aggravate the shape of nose and make it more difficult to correct. 27 Here comes the role of fat filling which can as previously mentioned improve and remodel the scar to ameliorate the outcome with low complication rates.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The other three studies reviewed by Khan et al were retrospective case series of rhinoplasty patients who did not receive postoperative splints. 13 15 Across 2385 total patients, the collective results demonstrated that splinting was not necessary to achieve desirable aesthetic outcomes. Taken in consideration with the previous study described, the efficacy of compression therapy after rhinoplasty may depend on the method of application, with evidence favoring elastic bandaging over nasal splinting to reduce edema and ecchymosis postoperatively.…”
Section: Uses In Facial Surgerymentioning
confidence: 99%
“…Use of various materials like aluminum, Orthoplast 3 , fiberglass 4 , plaster of Paris (POP), polyvinyl siloxane 5 , and thermoplastic materials as nasal splints including three-dimensional (3D)-printed splints 6 have been documented in the literature. Many of these splints are bulky, time-consuming to fabricate, expensive, cumbersome, and have reported incidences of contact dermatitis and epidermolysis 7 . Moreover, these splints can be maintained only for a short duration and cannot be retained if the situation warrants prolonged stabilization and immobilization.…”
Section: Introductionmentioning
confidence: 99%